2019
DOI: 10.21608/agro.2019.5676.1118
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Systems of Sunflower with Peanut under Different Irrigation Regimes and Potassium Fertilizer Levels

Abstract: T WO FIELD experiments were conducted at the research farm of Ismailia Governorate, Egypt during 2016 and 2017 summer seasons. This study was used to determine the suitable spatial arrangement of sunflower and peanut in an intercropping system under three irrigation water levels and three fertilizer (K) levels on yield, the land and water equivalent ratios and farmer's net income. The three irrigation treatments (0.7, 1.0 and 1.2ETo), the three K fertilizer levels (57, 86 and 114K 2 O kg/ha) and the four inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…The application of K-Si under water deficiency not only increase WER but also improved LER. These results are in agreement with the findings of Ouda et al (2018a), who found that the application K2O fertilizer at the highest level (114 kg/ha) under moderate water stress (1.0 ETo) increased LER values as compared to the lowest level of K2O fertilizer (50 kg/ha) under full irrigation (1.2 ETo) in peanut /sunflower intercropping system. Abd-Allah et al (2021), who found that the value of LER under the application of 200 ppm potassium silicate and irrigation treatment 100% ETo was higher than its counterpart value under irrigation with 120% ETo and no spraying in both growing seasons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The application of K-Si under water deficiency not only increase WER but also improved LER. These results are in agreement with the findings of Ouda et al (2018a), who found that the application K2O fertilizer at the highest level (114 kg/ha) under moderate water stress (1.0 ETo) increased LER values as compared to the lowest level of K2O fertilizer (50 kg/ha) under full irrigation (1.2 ETo) in peanut /sunflower intercropping system. Abd-Allah et al (2021), who found that the value of LER under the application of 200 ppm potassium silicate and irrigation treatment 100% ETo was higher than its counterpart value under irrigation with 120% ETo and no spraying in both growing seasons.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with the findings of Gomaa et al ( 2021) who mentioned the that oil percentage recorded the highest values with irrigation after depletion of 40% of available soil water. Ouda et al (2018a) stated that the oil percentage in peanut seeds was increased under irrigation with 100% ETo, compared to the application of 120% ETo. Although sesame is a drought-resistant crop, water stress affects sesame growth, capsule development, and final yield (Wang et al, 2016)..…”
Section: Discussionmentioning
confidence: 99%